2021
DOI: 10.3389/fphar.2021.762182
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nigella sativa, Camellia sinensis, and Allium sativum as Food Additives on Metabolic Disorders, a Literature Review

Abstract: Objective: Metabolic disorders (MD) can disturb intracellular metabolic processes. A metabolic disorder can be resulted from enzyme deficits or disturbances in function of various organs including the liver, kidneys, pancreas, cardiovascular system, and endocrine system. Some herbs were used traditionally for spices, food additives, dietary, and medicinal purposes. Medicinal plants possess biological active compounds that enhance human health. We aimed to provide evidence about therapeutic effects of some medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 124 publications
(124 reference statements)
0
12
0
Order By: Relevance
“…For example, studies have shown that daily intake of red yeast rice can reduce LDL-C levels from 15% to 25% ( 13 ). In addition, glucomannan ( 14 , 15 ), probiotics ( 14 , 16 ), garlic ( 17 ), berberine ( 18 ), omega-3 (ω′-3) and fatty acids ( 19 ), also have a positive effect on improving MetS.…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies have shown that daily intake of red yeast rice can reduce LDL-C levels from 15% to 25% ( 13 ). In addition, glucomannan ( 14 , 15 ), probiotics ( 14 , 16 ), garlic ( 17 ), berberine ( 18 ), omega-3 (ω′-3) and fatty acids ( 19 ), also have a positive effect on improving MetS.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the literature, when the catechin and epigallocatechin gallate contents of white and green tea were compared, it was higher in green tea (12,(24)(25)(26). Furthermore, these results that showed higher catechin proportions found in white tea could explain its high biological activities (anti-oxidant, anti-inflammatory, anti-cancer, anti-diabetic, anti-microbial, and reduced cardiovascular diseases) in comparison to green and black teas (11,(27)(28). In conclusion, the literature reviews have shown that there are no detailed scientific studies on white, green, and black tea grown in Turkey and white tea has been considered as requiring clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Many scientific studies have demonstrated that N. sativa has a broad spectrum of positive pharmacological effects, including antiviral ( 10 ), anti-inflammatory ( 11 ), hypotensive ( 12 ), hypoglycemic ( 13 ) and antitumor ( 14 ) effects. These biological properties are related to the abundance of several phytochemicals, including thymoquinone, terpenes, saponins, flavonoids, and essential oils ( 8 , 15 ). These promising active ingredients and their biological properties make N. sativa a powerful natural candidate for the prevention and control of diseases.…”
Section: Introductionmentioning
confidence: 99%